Post COVID-19 river quality: challenges ahead! - Ibrahim, Izihan; Mustafa, Maizatun; Abd Ghani, Hj. Mansor; Kailasam, Kalithasan; Al-Khatib, Ma'an Fahmi Rashid (2020)
MCO has been keeping humans locked in their homes-- which also means away from the nature.